Os povos indígenas e sua produção acadêmica no âmbito do Programa de Ações Afirmativas da UFSCar - Momo, Margarida Etsuko Endo (Universidade Federal de São Carlos, 2019)
This study analyzes and characterizes the monographs presented by native Brazilian people graduated between 2014 and 2017 who ingress on undergraduate courses through the Affirmative Actions Program of the National University of São Carlos. The objective was to verify which knowledge were brought by native Brazilian students of different ethnicities at their monographs and their collaboration to a greater respect of diversity and democracy in Brazil. Eight monographs were selected and read and according to the issues addressed it was analyzed the thematic focus, the theoretical and methodological references, the procedures adopted for data collection, the systematization of the results and the whole undergraduate process of each student. This analysis considers that in a democratic society the inclusion of minority citizens - e.g. the native Brazilian people – cannot rely only on their access to formal education and with their presence at the university, the education process should be modified valuing their culture, their knowledge and their lifestyle – opposing the commonly ethnocentric practice that has always sought to “civilize” them. It was possible to observe that regardless the undergraduate course most works presented themes valued by their ethnic groups – such as legends, myths, rites and games. In addition, it was observed that they used the traditional approaches of their culture to account of the history of their people and the struggles to delimitate and description of their lands and alternative ways to geographical localization.
Native brazilian and their academic production regarding Affirmative Actions Program at UFSCar
Keywords: Movimento Social Indígena; Educação indígena; Vestibular indígena; Native Brazilian Social Movement; Native brazilian education; Indigenous college entrance examination; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS SOCIAIS APLICADAS